Perawatan Full Overdenture Rahang Atas dan Rahang Bawah dengan Retensi Coping Logam - Bimo Rintoko (Lembaga Penelitian Universitas YARSI, 2017)
This case will study discussed full overdenture treatment in patient with partial edentulous upper jaw and lower jaw. Understand the treatment of full overdenture by using metal coping retention. 53 years old woman as a housewife comes with a chief complain of missing teeth and a lot of damage teeth that cannot be used to eat. Preliminary treatment and endodontic treatment on 13, 11, 21, 35, 33, 31, 41, 43. Next decuspation all remaining teeth on 13, 11, 21, 22, 35, 33, 31, 41, 43. On 13, 11, 21, 35, 33, 31, 41, 43 using a single coping with retentive attachment (single attachment). Treatment full overdenture using metal coping retention may be an alternative treatment in partian edentulous maxilla and mandibula.